Pengembangan Media Articulate Storyline Berbasis Kearifan Lokal Banyuwangi pada Materi Menyimak Siswa Sekolah Dasar - Mukhlisotin, Ana Yunita; Istiq’faroh, Nurul; Putra, Bintang Rostanto (Innovations in Multidisciplinary Education Journal, 2026)
This research aims to develop interactive learning media based on Articulate Storyline integrated with Banyuwangi local wisdom to improve the listening skills of third-grade elementary school students. The main problem underlying this research is the low focus of students and the lack of innovative media at SDN Lancar Abadi. The method used is Research and Development (R&D) with the ADDIE model. The research results show a validity level from material experts of 100% (Very Feasible). The practicality test by teachers obtained a score of 100% and student responses were 98.1% (Very Practical). The conclusion of this research is that the developed media is valid and practical to use as an innovative solution in Indonesian language learning in elementary schools.